Meta-Analysis of Therapy of Cinobufacini Capsule Adjunct with First-Line Platinum-Based Chemotherapy for the Treatment of Advanced NSCLC. (23rd August 2021) - Peng, Wenpan; Xu, Yong; Feng, Fanchao; Gu, Cheng; Wang, Zhichao; Han, Di; Zhou, Xianmei; He, Hailang
Abstract : Background . Cinobufacini capsule, an anticancer traditional Chinese patent medicine, has been widely used as adjunctive treatment to platinum-based chemotherapy in patients with advanced NSCLC. Purpose . To evaluate the efficacy and safety of cinobufacini capsule combined with first-line platinum-based chemotherapy for advanced NSCLC. Study Design . A systematic review and meta-analysis of eight outcome measures selected for this study were performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Methods . A comprehensive literature search was conducted in 7 electronic databases to identify all the relevant randomised controlled trials. Cochrane handbook 5.1.0 was applied to evaluate the quality of included trials, and the RevMan 5.3 and Stata 15.1 software were used to combine the trials for data analysis and assess the publication bias. Results . From the 19 studies reviewed, a total of 1, 564 patients were included. Compared with first-line platinum-based chemotherapy alone, cinobufacini capsule combined with chemotherapy showed significant effects in improving ORR (RR = 1.49, 95% CI (1.33, 1.66)), 1-year survival rate (RR = 1.44, 95% CI (1.28, 1.63)), and 2-year survival rate (RR = 1.78, 95% CI (1.42, 2.22)), raising the percentages of CD3 + cells (SMD = 1.25, 95% CI (1.05, 1.45)), CD4 + cells (SMD = 1.52, 95% CI (1.33, 1.71)), and ratio of CD4 + /CD8 + (SMD = 1.36, 95% CI (1.17, 1.54)), and reducing chemotherapy toxicity including leukopenia (RR = 0.61, 95% CI (0.51, 0.72)), thrombocytopenia (RR = 0.52, 95% CI (0.41, 0.67)), and vomiting (RR = 0.79, 95% CI (0.70, 0.88)). Conclusion . Cinobufacini capsule may increase the therapeutic effectiveness, improve cellular immune function, and reduce the toxicity of first-line platinum-based chemotherapy in patients with NSCLC. These results require confirmation by further rigorously designed randomised controlled trials (RCTs).